Answer:
B
Explanation:
Let first number = x
Second number = y
Twice a number = 2*x = 2x
The sum of twice a number and another number is 24
2x + y = 24 -----------------------(I)
The difference of twice the first number and the other number is 12.
2x - y = 12 ----------------------(II)
Add equation (I) & (II) and y will be eliminated and we can find the number 'x'
(I) 2x + y = 24
(II) 2x - y = 12 {Now add the two equations}
4x = 36
Divide both sides by 4
4x/4 = 36/4
x = 9
Plug in the value of 'x' in equation (I)
2*9 + y = 24
18 + y = 24
Subtract 18 from both sides
18 + y - 18 = 24 - 18
y = 6
The numbers are 9, 6